2018
DOI: 10.1177/2056305118784770
|View full text |Cite
|
Sign up to set email alerts
|

The Clickwrap: A Political Economic Mechanism for Manufacturing Consent on Social Media

Abstract: The clickwrap is a digital prompt that facilitates consent processes by affording users the opportunity to quickly accept or reject digital media policies. A qualitative survey analysis was conducted (N = 513), assessing user interactions with the consent materials of a fictitious social media service, NameDrop. Findings suggest that clickwraps serve a political economic function by facilitating the circumvention of consent materials. Herman and Chomsky's notion of the "buying mood" guides the analysis to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 35 publications
(38 reference statements)
0
22
0
5
Order By: Relevance
“…In the consent context, the clickwrap exemplifies this issue. A clickwrap "is a digital prompt that enables the user to provide or withhold their consent to a policy or set of policies by clicking a button, checking a box, or completing some other digitally mediated action suggesting "I agree" or "I don't agree" (Obar and Oeldorf-Hirsch, 2018). It is often presented using an appealing agree button, above a less-appealing, harder to see link (not a button) to policies.…”
Section: Unpacking the Consent Challengementioning
confidence: 99%
See 2 more Smart Citations
“…In the consent context, the clickwrap exemplifies this issue. A clickwrap "is a digital prompt that enables the user to provide or withhold their consent to a policy or set of policies by clicking a button, checking a box, or completing some other digitally mediated action suggesting "I agree" or "I don't agree" (Obar and Oeldorf-Hirsch, 2018). It is often presented using an appealing agree button, above a less-appealing, harder to see link (not a button) to policies.…”
Section: Unpacking the Consent Challengementioning
confidence: 99%
“…It is often presented using an appealing agree button, above a less-appealing, harder to see link (not a button) to policies. Clickwraps serve an agenda-setting function in this respect, as users, already directed by the aforementioned desire to access services, reading from top-to-bottom, see the appealing button first and likely miss the less-appealing policy links (Obar and Oeldorf-Hirsch, 2018). The clickwrap provides users with a "fastlane to monetized sections of services, as opposed to diverting attention to dissent possibilities" (Obar and Oeldorf-Hirsch, 2018).…”
Section: Unpacking the Consent Challengementioning
confidence: 99%
See 1 more Smart Citation
“…Two other point‐of‐disclosure patterns companies use to normalize the disclosure of personal information, and the prevailing metaphors for personal information and big data, illustrate how companies construct preferences. First, the imposition of “clickwraps”—the pop‐up boxes that force individuals to accept or decline various terms—between users and their desired content and services discourages the necessary reflective engagement with data disclosures that are at the heart of the notice and choice privacy framework (Good, 2007; Obar & Oeldorf‐Hirsch, 2018). Clickwraps serve as an effective political economic mechanism to manufacture consent, diminishing interest and understanding of corporate data policies and funneling consumers toward data disclosure.…”
Section: Dark Patterns: the Construction Of Privacy “Preferences”mentioning
confidence: 99%
“…Clickwraps are digital prompts that allow users to agree to privacy policies without seeing them. Obar and Oeldorf-Hirsch (2018) found that clickwraps facilitated circumvention of consent policies, allowing social media companies to manufacture consent by making it possible to consent to a privacy policy without seeing a single word of it on screen. However, from a legal standpoint clicking Agree means users opt in to Facebook's data policy and provides proof that they have read and understood the policy in its entirety.…”
Section: Introductionmentioning
confidence: 99%